Behavioural Change and the Temporal Ordering of Eating Practices: A UK–Spain Comparison - Southerton, Dale; Díaz-Méndez, Cecilla; Warde, Alan (The International Journal of Sociology of Agriculture and Food, 2012)
Dominant policy approaches to changing behaviour typically address the topic by way of the attitudes, beliefs and intentions of individuals. Their analytic value is compromised by the limited success of policies based upon such an understanding. In light of the expectation that, inter alia, mitigation of climate change will require radical changes in food consumption, we make some suggestions about the value of alternative models of behaviour and data sources that focus on the temporal ordering of the practice of eating. We review selectively the social scientific literature on the relationship between time and eating. Following a brief review of theoretical accounts of time and its significance in relation to eating, we reprise the conceptual apparatus for understanding temporality, with its distinctions between duration, sequence, periodicity, tempo and synchronization. The multiple temporalities of eating are examined in relation to empirical evidence, primarily through cross-cultural comparative analysis of Spain and the UK. We argue that detailed empirical attention to time and timings can provide important insights into patterns of food consumption, and that addressing the temporal ordering of practices presents opportunities for achieving substantial shifts in behaviours.